Disciplinary school exclusion: pushing children over the edge - Taubman, Katie (2022)
Disciplinary school exclusion, alongside the issue of school discipline, has been identified as a problem in education since the mid-1980s (Department for Education and Skills, 1985). Education in England has been exclusive since its conception, beginning with the exclusion of more than 50% of the population from schooling when it was only available to the upper and middle ‘classes’ (Gibbs, 2022). There is a distinct gap in the literature exploring disciplinary school exclusion as an object constructed through discourse, using a discourse analytic approach.